ANALISIS GAP (KESENJANGAN) TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN PERAWAT DI INSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT SETIA BUDI RIMBO BUJANG, TEBO - Ramadhita Fadhilah; Andi Subandi; Rts Netisa Martawinarti; Dini Rudini; Yosi Oktarina (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Patient satisfaction is an essential indicator in evaluating the quality of nursing services in the Emergency Department (ED). Service quality can be assessed by comparing patients’ expectations and perceptions using the SERVQUAL instrument through gap analysis; the smaller the gap, the better the perceived quality of care. This study aimed to analyze patient satisfaction based on the difference between expectation and perception scores of nursing services at the Emergency Department of Setia Budi Rimbo Bujang Hospital. This quantitative study employed a cross-sectional design involving 101 respondents selected through accidental sampling. Data were collected using a SERVQUAL questionnaire covering five dimensions: tangible, reliability, responsiveness, assurance, and empathy. The results revealed negative gaps across all dimensions, with the largest gaps in responsiveness and empathy and the smallest in tangible. These findings indicate the need to improve service quality, particularly in nurses’ responsiveness and empathy.